Training in Inter-Personal Skills / TIPS for Managing People at Work - Robbins Stephen P (Prentice Hall International, 1989)
Preface, Skills: An Introduction, A Point of Departure: Self-Awareness, Listening, Goal Setting, Providing Feedback, Appraising Performance, Disciplining, Delegating, Using Oral Persuasion, Politicking, Running a Group Meeting, Resolving Conflicts, Integration, References.
Preface, Skills: An Introduction, A Point of Departure: Self-Awareness, Listening, Goal Setting, Providing Feedback, Appraising Performance, Disciplining, Delegating, Using Oral Persuasion, Politicking, Running a Group Meeting, Resolving Conflicts, Integration, References.